Commentary : current status and issues regarding pre-processing of fnirs neuroimaging data : an investigation of diverse signal filtering methods within a general linear model framework - Bizzego, Andrea (2020)
We read with great interest the manuscript from Pinti et al. (2019), which aimed to shed a light on one of the main open topics in neuroimaging: the definition of reproducible and standardized pipelines for the preprocessing of functional Near InfraRed Spectroscopy (fNIRS) signals. In particular, Pinti and colleagues focused on the filtering step, evidencing a high heterogeneity of filter types adopted and settings that could undermine the reproducibility of the studies.